2011
DOI: 10.1002/14651858.cd009085.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent iron supplementation for improving nutrition and development in children under 12 years of age

Abstract: Intermittent iron supplementation for improving nutrition and development in children under 12 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
151
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(174 citation statements)
references
References 80 publications
2
151
2
6
Order By: Relevance
“…Profilaktik olarak kullanılan demir günlük olarak oral yolla verilmektedir (günlük demir profilaksisi). Son zamanlarda intermitan demir profilaksisi olarak adlandırılan haftada bir veya iki kez demir kullanımının da etkin olduğunu bildiren çalışmalar yayınlanmaktadır (13)(14)(15)(16). Oral yoldan alınan demirin ilk dozundan sonra enterositlerden demir ve diğer minerallerin emiliminin geçici olarak blokaja uğramasından dolayı günlük demir kullanımı ile intermitan demir kullanımlarının benzer şekilde barsaktan emildiğini bildiren çalışmalar vardır (17,18).…”
Section: Discussionunclassified
“…Profilaktik olarak kullanılan demir günlük olarak oral yolla verilmektedir (günlük demir profilaksisi). Son zamanlarda intermitan demir profilaksisi olarak adlandırılan haftada bir veya iki kez demir kullanımının da etkin olduğunu bildiren çalışmalar yayınlanmaktadır (13)(14)(15)(16). Oral yoldan alınan demirin ilk dozundan sonra enterositlerden demir ve diğer minerallerin emiliminin geçici olarak blokaja uğramasından dolayı günlük demir kullanımı ile intermitan demir kullanımlarının benzer şekilde barsaktan emildiğini bildiren çalışmalar vardır (17,18).…”
Section: Discussionunclassified
“…In a systematic review, De-Regil LM (35) showed that intermittent iron supplementation is efficacious to improve haemoglobin concentrations and reduce the risk of anaemia or iron deficiency in children younger than 12 years of age when compared with a placebo or no intervention. Given the prior success on controlling iron and zinc deficiencies, vitamin D enrichment seems a logical next step in food supplementation to improve the nutritional status of Mexican children.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to fully establish a causal relationship between ID and poor neurodevelopment due to many confounding factors, iron is important for neuronal energy metabolism, metabolism of neurotransmitters, myelination, and memory function. There are some reports of improvement in cognitive functions with treatment of IDA 5 . Iron is approximately distributed as 73% in haemoglobin, 12% in storage complexes (ferritin and haemosiderin) and 15% in enzymes.…”
Section: Ironmentioning
confidence: 99%
“…Intermittent iron supplementation reduces the risk of ID and IDA in children compared to placebo or no intervention, but it is less effective than daily supplementation. Intermittent supplementation is therefore a viable public health supplementation option 5 . It is recommended to provide 25mg of elemental iron to children 24-59 months and 75mg for 5-12 year old children weekly for 12 weeks and recommence another 12 week cycle after a 3 month gap (total of 24 months).…”
Section: Iron Supplementationmentioning
confidence: 99%
See 1 more Smart Citation